THE FORECASTING OF CURLY RED CHILI PRICE (Capsicum annum L.) IN BENGKULU CITY - Septarena, Refi; Arianti, Nyayu Neti; Sumantri, Bambang (Journal of Agri Socio Economics and Business, 2025)
Curly red chili is one of the contributors to inflation because the price of curly red chili fluctuates and is influenced by the season.  Fluctuations in chili prices will result in economic instability and increased inflation which will lead to a decrease in people's ability to meet their daily needs, thereby increasing poverty. This research was conducted in Bengkulu City because red chili production continues to decline due to the conversion of agricultural land into housing. The data used is time series data on the price of curly red chili at the retailer level per day in March 2021 – May 2025 which was converted into monthly data by averaging. This data was obtained from the National Food Agency. Judging from the pattern of chili price developments in August - November 2025, there was an increase in prices, while in August - November 2024 there was a decrease. At the end of 2024, prices are expected to fall due to good weather conditions so that the harvest of curly red chili can be maximized.  Meanwhile, at the end of 2025, prices will increase due to weather conditions that will enter the rainy season. From March 2021 to July 2024, the highest price of curly red chili was IDR 84,000/Kg, namely in July 2022, while the lowest price was IDR 22,000/Kg in June 2021. The price of curly red chili in June 2025 - December 2025 was remained drop at  price of IDR 28,000/Kg, it could fluctuate due to various factors impacting chili cultivation.